Functional profiling of Syzygium aromaticum-associated bacteria reveals PGPR traits for tropical biofertilizer development - HENRY KESAULYA; WAHYU HIDAYAT; RUMELLA SIMARMATA; JOGENEIS PATTY (Society for Indonesian Biodiversity, 2025)
Abstract. Kesaulya H, Hidayat W, Simarmata R, Patty J. 2025. Functional profiling of Syzygium aromaticum-associated bacteria reveals PGPR traits for tropical biofertilizer development. Biodiversitas 26: 6130-6139. Syzygium aromaticum (clove) is a tropical spice of major economic and ecological importance in Indonesia, yet the microbial communities associated with its cultivation remain poorly characterized. Harnessing native Plant Growth-Promoting Rhizobacteria (PGPR) offers a sustainable alternative to chemical inputs and supports resilient agroecosystems. This study explored the biofertilizer potential of bacterial strains isolated from S. aromaticum-growing regions in Central Maluku, Indonesia. Rhizospheric and endophytic isolates were characterized using physiological assays and 16S rRNA sequencing to assess key PGPR traits, including auxin production, phosphate solubilization, nitrogen fixation, and enzymatic activities relevant to nutrient cycling and stress tolerance. Eleven isolates were obtained, with greater diversity from the rhizosphere (9 isolates) than from leaves (2 isolates). Screening demonstrated multiple plant-beneficial traits, including indole-3-acetic acid production, phosphate solubilization, and growth in nitrogen-free medium, complemented by hydrolytic enzyme activities and catalase-based stress tolerance. Three isolates showed particularly strong multifunctional profiles: T5RCHM21 (high IAA, phosphate solubilization, nitrogen-fixation trait, broad pH tolerance), T6RCHM3 (highest phosphate solubilization and cellulolytic activity), and T4RCHM3 (very strong catalase with additional enzymatic indices). 16S rRNA analysis grouped isolates mainly within Bacillus, with Brevibacterium, and Klebsiella, supporting phenotype-driven selection and future field validation for practical application.